CONVENTIONAL METHODS OF DETERMINING VALIDITY: ANALYSIS FROM AN ISLAMIC PERSPECTIVE (International Journal of Islamic Business, 2016)
This paper aims to identify the conventional methods of determining validity. Then, analyze the methods from the Islamic perspective. The methods of determining validity here refer to methods that can ensure the instrument’s validity or measurement and data validity. Instrument’s validity or measurement and data validity leads to results and findings which are true. The question is what are the methods of determining validity contained in conventional research? Are these methods appropriate for research related to the affairs of Islam and the Muslims? This paper aims to answer both of these questions through a textual analysis on a few literatures. For the first question, this paper discusses the identified six conventional methods of determining validity. Such methods include methods for determining validity of the instrument or measurement and methods of determining data validity. As for the second question, this paper concludes that the conventional methods of determining validity is inappropriate as the method of determining validity for research related to the affairs of Islam and the Muslims.